Bestandsaufnahme und Analyse der Ansätze zum Umgang mit Airbnb in ausgewählten europäischen Destinationen - Anna Klein; Annegret Wittmann-Wurzer; Nicola Zech (IUBH Internationale Hochschule, 2020)
– Nowadays Airbnb represents a popular subject both within professional journals as well as on industry platforms. Most of them focus on the aspect of the competition of Airbnb and the hospitality industry - hotels, guesthouses as well as apartments. This research paper focuses a slightly different aspect: approaches of selected European destinations within their attitude towards Airbnb. Within this research a combined survey from various angles is conducted: identification of the 10 European destinations most represented on Airbnb (by offered accommodation - reference date Oct 15, 2018), potential course of action from destination management point of view as well as enforced course of action within the selected destination. As part of the analysis a ranking of the range of Airbnb offers within the correspondent destinations is set up.
Keywords: L19; L83; 650; Sharing Economy; Beherbergungsgewerbe; Destinationsmanagement; Airbnb